2016
DOI: 10.1111/dme.13152
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of taking oral medications for the treatment of Type 2 diabetes mellitus: a systematic review and meta‐synthesis of qualitative studies

Abstract: AimsTo explore patients' perceptions and experiences of taking oral medications for the pharmacological management of Type 2 Diabetes Mellitus (Type2DM). MethodsCinahl, EMBASE, Medline and PsycINFO databases were searched in 2014 to identify qualitative studies exploring patients' perceptions or experiences of taking medications for the management of Type2DM. Key concepts and themes were extracted and synthesised using meta-ethnography. ResultsEight studies were included. Primary study findings were synthesise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 33 publications
3
68
0
1
Order By: Relevance
“…The present findings are also consistent with previous studies, in which PC physicians and specialists emphasized the need to lower the number of daily diabetic medications to improve patients’ adherence, clinical outcomes and quality of life,37 whereas T2DM patients considered adjusting medication regimen to their daily lives more essential,22 stating that a more flexible dosing regimen that could be adapted to them would be an effective strategy to improve their adherence to antidiabetic therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present findings are also consistent with previous studies, in which PC physicians and specialists emphasized the need to lower the number of daily diabetic medications to improve patients’ adherence, clinical outcomes and quality of life,37 whereas T2DM patients considered adjusting medication regimen to their daily lives more essential,22 stating that a more flexible dosing regimen that could be adapted to them would be an effective strategy to improve their adherence to antidiabetic therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, recent evidence indicates that T2DM patients’ involvement in the disease management may improve adherence to therapy 22. Thus, some studies reported that patients increased their engagement and motivation if they perceived their preferences are considered in the development of management strategies, and consequently, medication adherence and clinical outcomes may improve 23…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to assess the type of adherence when determining the psychosocial factors that are involved. Besides illness representations and beliefs about medicines, it is important to study the impact of strategies to promote adherence such as reminders and dose organizers in patients with unintentional non‐adherence (McSharry, McGowan, Farmer, & French, ). Such a differentiation may help optimize interventions to the particular type of non‐adherence exhibited by the patient before it becomes established, during the course of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the treatments for these disorders are limited. Available medications are frequently associated with poor tolerability and patient compliance, thus resulting in sub-optimal outcomes [1,2]. The need for additional drugs or alternative treatments that are easily administered has become an urgent issue in biomedical research.…”
Section: Introductionmentioning
confidence: 99%